2010
DOI: 10.1111/j.1469-7610.2010.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

An item response theory analysis of the Parenting Stress Index‐Short Form with parents of children with autism spectrum disorders

Abstract: The parent-child dysfunctional interaction and difficult child subscales of the PSI-SF scale should be used with caution with parents of young children with ASD. More research is required to examine PSI-SF content validity, at least among parents of children with ASD and perhaps parents of children with other disabilities as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 22 publications
0
67
2
Order By: Relevance
“…We also focused exclusively on maternal-as opposed to paternal-stress, the idea being that mothers and fathers may differ in regard to the amount and correlates of their stress (Krauss, 1993). Limitations of the PSI-SF based on age (Abidin, 1990) and autism (Zaidman-Zait et al, 2010) should also be noted, although we attempted to check for both with our follow-up analyses. Our main limitation, however, most likely entailed this study's cross-sectional nature.…”
Section: Discussionmentioning
confidence: 98%
“…We also focused exclusively on maternal-as opposed to paternal-stress, the idea being that mothers and fathers may differ in regard to the amount and correlates of their stress (Krauss, 1993). Limitations of the PSI-SF based on age (Abidin, 1990) and autism (Zaidman-Zait et al, 2010) should also be noted, although we attempted to check for both with our follow-up analyses. Our main limitation, however, most likely entailed this study's cross-sectional nature.…”
Section: Discussionmentioning
confidence: 98%
“…Validity and reliability are reported in the manual, along with a .94 correlation between the short and long form. Recent reliability estimates ranged from .84 to .93 for the Parental Distress subscale (Zaidman-Zait et al, 2010). Internal consistency between subtests and the total score was .90 and remained the same 1 yr later (Haskett, Ahern, Ward, & Allaire, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…While the reasons for this finding are unclear, it may be because the difficult child subscale of the parental stress index focuses more on how bothered parents are by their children's behaviors rather than the difficulty of child behaviors themselves. In fact, a series of studies assessing the PSI-SF found the difficult child subscale to be the least discriminating in terms of types of parental stress (Zaidman-Zait et al 2010, 2011.…”
Section: Outcomementioning
confidence: 99%